Przyszłość opieki zdrowotnej w Polsce – nowe horyzonty - Czerska, Iwona; Trojanowska, Angelika; Korpak, Tetiana (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2019)
The aim of the study is to present new healthcare solutions in Poland. The type of research methodology used is the analysis of literature and websites presenting modern solutions, including IT, in health protection. The concept of eHealth was discussed, focusing on the P1 platform and electronic medical records: e-ZLA, e-prescription and e-referral. The following aspects were pointed out: functionality, efficiency, safety, as well as technical and mental barriers related to the introduction of electronic medical records. Health needs maps were presented in the context of new challenges. Attention was drawn to the ongoing works on the new shape of maps, as well as their practical meaning for creating current health policy at the regional level. Innovative solutions in the mobile patient service were presented. The essence of coordinated care in the context of building links between basic health care, outpatient health care and hospitality (cooperation triangle) was discussed. The issue of a holistic approach to the needs of the patient as a consumer of health services was raised
Keywords: healthcare; e-health; health needs maps; coordinated care